Faktor-Faktor yang Berhubungan dengan Kejadian Preeklampsia pada Ibu Hamil di RSU Bahagia Kota Makassar - St Subriani; Samsir syam (LPPM Universitas Harapan Bangsa, 2023)
The incidence of preeclampsia in Indonesia ranges from 3-10% of all pregnancies. The results of an initial study at the Happy Hospital (RS) in Makassar City, for data on the incidence of preeclampsia from January to December 2020 as many as 48 people (37.0%) cases. The purpose of this study was to determine the factors associated with the incidence of preeclampsia in mothers. pregnant at Happy Makassar Hospital. This study uses analytic methods with a Case Control approach to see the factors associated with the independent variable and the dependent variable. The population in this study were all pregnant women who had a pregnancy check-up in April 2021, totaling 90 women. The sampling technique was carried out in total sampling, namely taking the entire population to be sampled. From the results of statistical tests using the Chi-Square test (fisher' exact test) obtained the results of the mother's age (Pvalue = 0.399 < α = 0.05. OR = 0.272 times). History of preeclampsia (Pvalue = 0.573 < α = 0.05. OR = 0.268 times). Parity (Pvalue = 0.446 < α = 0.05. OR = 0.318 times). This means that there is no significant relationship with the incidence of preeclampsia. The conclusion in this study was that there was no significant relationship between maternal age, history of preeclampsia and the incidence of preeclampsia.